Genotype-phenotype correlation in L1 associated diseases. Issue 5 (May 1998) - Fransen, E; Van Camp, G; D'Hooge, R; Vits, L; Willems, P J
Abstract : The neural cell adhesion molecule L1 (L1CAM) plays a key role during embryonic development of the nervous system and is involved in memory and learning. Mutations in the L1 gene are responsible for four X linked neurological conditions: X linked hydrocephalus (HSAS), MASA syndrome, complicated spastic paraplegia type 1 (SP-1), and X linked agenesis of the corpus callosum. As the clinical picture of these four L1 associated diseases shows considerable overlap and is characterised by Corpus callosum hypoplasia, mental Retardation, Adducted thumbs, Spastic paraplegia, and Hydrocephalus, these conditions have recently been lumped together into the CRASH syndrome. We investigate here whether a genotype-phenotype correlation exists in CRASH syndrome since its clinical spectrum is highly variable and numerous L1 mutations have been described. We found that (1) mutations in the extracellular part of L1 leading to truncation or absence of L1 cause a severe phenotype, (2) mutations in the cytoplasmic domain of L1 give rise to a milder phenotype than extracellular mutations, and (3) extracellular missense mutations affecting amino acids situated on the surface of a domain cause a milder phenotype than those affecting amino acids buried in the core of the domain.